Accurate Sampling with Noisy Forces from Approximate Computing - Rengaraj, Varadarajan; Lass, Michael; Plessl, Christian; Kühne, Thomas (Computation)
In scientific computing, the acceleration of atomistic computer simulations by means of custom hardware is finding ever-growing application. A major limitation, however, is that the high efficiency in terms of performance and low power consumption entails the massive usage of low precision computing units. Here, based on the approximate computing paradigm, we present an algorithmic method to compensate for numerical inaccuracies due to low accuracy arithmetic operations rigorously, yet still obtaining exact expectation values using a properly modified Langevin-type equation.

Oracle complexity classes and local measurements on physical Hamiltonians - Gharibian, Sevag; Piddock, Stephen; Yirka, Justin (Proceedings of the 37th Symposium on Theoretical Aspects of Computer Science (STACS 2020))
The canonical problem for the class Quantum Merlin-Arthur (QMA) is that of estimating ground state energies of local Hamiltonians. Perhaps surprisingly, [Ambainis, CCC 2014] showed that the related, but arguably more natural, problem of simulating local measurements on ground states of local Hamiltonians (APX-SIM) is likely harder than QMA. Indeed, [Ambainis, CCC 2014] showed that APX-SIM is P^QMA[log]-complete, for P^QMA[log] the class of languages decidable by a P machine making a logarithmic number of adaptive queries to a QMA oracle. In this work, we show that APX-SIM is P^QMA[log]-complete even when restricted to more physical Hamiltonians, obtaining as intermediate steps a variety of related complexity-theoretic results. We first give a sequence of results which together yield P^QMA[log]-hardness for APX-SIM on well-motivated Hamiltonians: (1) We show that for NP, StoqMA, and QMA oracles, a logarithmic number of adaptive queries is equivalent to polynomially many parallel queries. These equalities simplify the proofs of our subsequent results. (2) Next, we show that the hardness of APX-SIM is preserved under Hamiltonian simulations (a la [Cubitt, Montanaro, Piddock, 2017]). As a byproduct, we obtain a full complexity classification of APX-SIM, showing it is complete for P, P^||NP, P^||StoqMA, or P^||QMA depending on the Hamiltonians employed. (3) Leveraging the above, we show that APX-SIM is P^QMA[log]-complete for any family of Hamiltonians which can efficiently simulate spatially sparse Hamiltonians, including physically motivated models such as the 2D Heisenberg model. Our second focus considers 1D systems: We show that APX-SIM remains P^QMA[log]-complete even for local Hamiltonians on a 1D line of 8-dimensional qudits. This uses a number of ideas from above, along with replacing the "query Hamiltonian" of [Ambainis, CCC 2014] with a new "sifter" construction.

Nonlinear focal mapping of ferroelectric domain walls in LiNbO3: Analysis of the SHG microscopy contrast mechanism - Spychala, K. J.; Mackwitz, P.; Rüsing, Michael; Widhalm, A.; Berth, Gerhard; Silberhorn, Christine; Zrenner, Artur (Journal of Applied Physics)

Selbstreguliertes Lernen - Können die das überhaupt? Gestaltung von Lernprozessen in berufsvorbereitenden Bildungsgängen. - Sloane, Peter F. E.; Daniel, Desiree; Meier, Karin; Schwabl, Franziska; Volgmann, Simone

Material Specific Predicting of the Optimal Joining Parameters for the Screw Blind Rivet Joining Process - Moritzer, Elmar; Hillemeyer, Johannes (73rd Annual Assembly of International Institute of Welding (IIW) and International Conference)

MANUFACTURING OF HYBRID COMPONENTS BY VARTM-PROCESS USING NEW SEALING TECHNIQUE DEVELOPED - Chalicheemalapalli Jayasankar, Deviprasad; Stallmeister, Tim; Wang, Zheng; Tröster, Thomas (Hybrid 2020 Materials and Structures)

PSΦ: Forschungsprogramm zur Studieneingangsphase im Physikstudium - Bauer, Anna; Lahme, Simon; Woitkowski, David; Vogelsang, Christoph; Reinhold, Peter (PhyDid B – Didaktik der Physik – Beiträge zur DPG-Frühjahrstagung)

Vorerfahrungen, Einstellungen und motivationale Orientierungen als mögliche Einflussfaktoren auf den Einsatz digitaler Werkzeuge im naturwissenschaftlichen Unterricht - Vogelsang, Christoph; Finger, Alexander; Laumann, Daniel; Thyssen, Christoph (Zeitschrift für Didaktik der Naturwissenschaften)

Entwicklung von Professionswissen und Unterrichtsperformanz im Lehramtsstudium Physik. Analysen zu valider Testwertinterpretation - Vogelsang, Christoph; Borowski, Andreas; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Kulgemeyer, Christoph; Reinhold, Peter; Riese, Josef; Schecker, Horst; Schröder, Jan (Zeitschrift für Pädagogik)
Angehende Physiklehrkräfte sollen im Rahmen ihres Studiums fachliches und fachdidaktisches Wissen erwerben, welches die Gestaltung lernförderlichen Unterrichts ermöglicht. Es ist allerdings empirisch nur wenig geklärt, wie sich dieses Wissen im Laufe des Studiums entwickelt und ob es zur Ausbildung von Handlungsfähigkeiten beiträgt. Um derartige Wirkungsaussagen treffen zu können, müssen Instrumente entwickelt werden, die eine valide Testwertinterpretation zulassen. In diesem Beitrag werden auf Basis von im Projekt Profile-P+ entwickelten Instrumenten Validitätsanalysen zur längsschnittlichen Entwicklung des Professionswissens von Physiklehramtsstudierenden im Verlauf des Bachelorstudiums und ihrer Fähigkeiten zur Planung und Reflexion von Physikunterricht sowie zum Erklären von physikalischen Sachverhalten vor und nach dem Praxissemester dargestellt. Neben Wissenstests kamen standardisierte Performanztests zum Einsatz. Die vorliegenden Ergebnisse sprechen dafür, dass die erhobenen Messwerte im Sinne von Wirkungsaussagen interpretiert werden können. (DIPF/Orig.)

Professionalisierung durch Portfolioarbeit – Ein Beitrag zur Erfassung der Reflexionskompetenz von Lehramtsstudierenden. - Stender, Jana; Schaper, Niclas; Vogelsang, Christoph; Watson, Christina (Lehrerbildung auf dem Prüfstand)

Performance-Oriented Testing and Training in Teacher Education - Vogelsang, Christoph; Borowski, Andreas; Kulgemeyer, Christoph; Riese, Josef; Reinhold, Peter; Schecker, Horst; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Schröder, Jan

Reflexionskompetenz trainieren: Unterrichtsvideographie als Werkzeug zur fachdidaktischen Begleitung im Praxissemester - Vogelsang, Christoph (Praxissemester (Religion) in NRW: Bilanz und Perspektiven)

Integrated All Optical Sampling of Microwave Signals in Silicon Photonics - Misra, Arijit; Kress, Christian; Singh, Karanveer; Preussler, Stefan; Scheytt, Christoph; Schneider, Thomas (2019 International Topical Meeting on Microwave Photonics (MWP))
Optical sampling of pseudo random microwave signals with sinc-shaped Nyquist pulse sequences has been demonstrated in an integrated silicon photonics platform. An electronic-photonic, co-integrated depletion type silicon intensity modulator with high extinction ratio has been used to sample the microwave signal with a sampling rate, which corresponds to three times its RF bandwidth. Thus, a sampling rate of 21 GSa/s is achieved with a 7 GHz modulator, with 3 dBm of differential input power.

Integrated source-free all optical sampling with a sampling rate of up to three times the RF bandwidth of silicon photonic MZM - Misra, Arijit; Kress, Christian; Singh, Karanveer; Preussler, Stefan; Scheytt, Christoph; Schneider, Thomas (Opt. Express)
Source-free all optical sampling, based on the convolution of the signal spectrum with a frequency comb in an electronic-photonic, co-integrated silicon device will be presented for the first time, to the best of our knowledge. The method has the potential to achieve very high precision, requires only low power and can be fully tunable in the electrical domain. Sampling rates of three and four times the RF bandwidths of the photonics and electronics can be achieved. Thus, the presented method might lead to low-footprint, fully-integrated, precise, electrically tunable, photonic ADCs with very high-analog bandwidths for the digital infrastructure of tomorrow.

Midinfrared Birefringence of Liquid Crystals, Polarimetry, and Intensity Modulators - Atorf, Bernhard; Auf der Landwehr, Chris Holm; Rennerich, Roman; Kitzerow, Heinz-Siegfried (The Journal of Physical Chemistry B)

Den Einsatz digitaler Medien im naturwissenschaftlichen Unterricht lehren - Untersuchung der Lehrinitiative Didaktik:digital im Spannungsfeld von standortübergreifender Wirkungsanalyse und standortspezifischer Evaluation - Vogelsang, Christoph (Hochschuldidaktik erforscht Qualität - Profilbildung und Wertefragen in der Hochschulentwicklung III)

Integrated transition edge sensors on titanium in-diffused lithium niobate waveguides - Höpker, Jan Philipp; Gerrits, Thomas; Lita, Adriana; Krapick, Stephan; Herrmann, Harald; Ricken, Raimund; Quiring, Viktor; Mirin, Richard; Nam, Sae Woo; Silberhorn, Christine; Bartley, Tim (APL Photonics)

Theory of an Optoelectronic Microwave Phase-locked Loop based on a MLL reference and MZM-based Optoelectronic Phase Detection - Bahmanian, Meysam; Scheytt, Christoph

Untersuchungen zum energetischen Verhalten von Kunststoffverarbeitungsprozessen auch im Rahmen von Energiemanagementsystemen - Gehring, Andreas

Entwicklung eines Modells zur Berechnung der initialen Aufschmelzvorgänge in gleichläufigen Doppelschneckenextrudern - Westhues, Kim Jacqueline